Development of 68Ga-Glycopeptide as an Imaging Probe for Tumor Angiogenesis. (7th April 2011) - Tsao, Ning; Wang, Chau-Hui; Her, Li-Jane; Tzen, Kai-Yuan; Chen, Jing-Yi; Yu, Dong-Fang; Yang, David J.
Abstract : Objective . This study was aimed to study tissue distribution and tumor imaging potential of 68 Ga-glycopeptide (GP) in tumor-bearing rodents by PET. Methods . GP was synthesized by conjugating glutamate peptide and chitosan. GP was labeled with 68 Ga chloride for in vitro and in vivo studies. Computer outlined region of interest (counts per pixel) of the tumor and muscle (at the symmetric site) was used to determine tumor-to-muscle count density ratios. To ascertain the feasibility of 68 Ga-GP in tumor imaging in large animals, PET/CT imaging of 68 Ga-GP and 18 F-FDG were conducted in New Zealand white rabbits bearing VX2 tumors. Standard uptake value of tumors were determined by PET up to 45 min. To determine blood clearance and half-life of 68 Ga-GP, blood samples were collected from 10 seconds to 20 min. Results . Radiochemical purity of 68 Ga-GP determined by instant thin-layer chromatography was >95%. Tumor uptake values (SUV) for 68 Ga-GP and 18 F-FDG in New Zealand white rabbits bearing VX2 tumors were 3.25 versus 7.04. PET images in tumor-bearing rats and rabbits confirmed that 68 Ga-GP could assess tumor uptake. From blood clearance curve, the half-life of 68 Ga-GP was 1.84 hr. Conclusion Our data indicate that it is feasible to use 68 Ga-GP to assess tumor angiogenesis.